2018
DOI: 10.1080/03639045.2018.1431656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of various solid carriers and spray drying on pre/post compression properties of solid SNEDDS loaded with glimepiride: in vitro-ex vivo evaluation and cytotoxicity assessment

Abstract: Development of self-nanoemulsifying drug delivery systems (SNEDDS) of glimepiride is reported with the aim to achieve its oral delivery. Lauroglycol FCC, Tween-80, and ethanol were used as oil, surfactant, and co-surfactant, respectively as independent variables. The optimized composition of SNEDDS formulation (F1) was 10% v/v Lauroglycol FCC, 45% v/v Tween 80, 45% v/v ethanol, and 0.005% w/v glimepiride. Further, the optimized liquid SNEDDS were solidified through spray drying using various hydrophilic and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…To each formulation, 30 mg PPK and 2.75 mg CRM were added. 5,21 The obtained results were correlated with the theoretical values of responses that were obtained through BBD.…”
Section: Design Of Experimentssupporting
confidence: 60%
See 4 more Smart Citations
“…To each formulation, 30 mg PPK and 2.75 mg CRM were added. 5,21 The obtained results were correlated with the theoretical values of responses that were obtained through BBD.…”
Section: Design Of Experimentssupporting
confidence: 60%
“…12,18 This indicated that the emulsions were found stable. 5,21 Moreover, cloud point temperature of emulsions was within the range of 85.34°C-96.32°C ( Table 3). The stability of emulsions above 37°C indicate that they will be stable in gastrointestinal tract (GIT) upon oral administration.…”
Section: Preliminary Investigation Of Formulationmentioning
confidence: 96%
See 3 more Smart Citations